2011
DOI: 10.1186/1471-2105-12-365
|View full text |Cite
|
Sign up to set email alerts
|

Simple Shared Motifs (SSM) in conserved region of promoters: a new approach to identify co-regulation patterns

Abstract: BackgroundRegulation of gene expression plays a pivotal role in cellular functions. However, understanding the dynamics of transcription remains a challenging task. A host of computational approaches have been developed to identify regulatory motifs, mainly based on the recognition of DNA sequences for transcription factor binding sites. Recent integration of additional data from genomic analyses or phylogenetic footprinting has significantly improved these methods.ResultsHere, we propose a different approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…The availability of genomic and transcriptomic data for many horticultural crops allows the identification of novel CREs using bioinformaticsbased and experimental approaches 11,90,91 . The de novo CRE discovery is based on sequence conservation that exists among groups of genes that are co-expressed as well as gene families within a single genome, and among orthologs of multiple species [91][92][93] .…”
Section: Strategies For Application Of Crispr/cas-mediated Cis-enginementioning
confidence: 99%
“…The availability of genomic and transcriptomic data for many horticultural crops allows the identification of novel CREs using bioinformaticsbased and experimental approaches 11,90,91 . The de novo CRE discovery is based on sequence conservation that exists among groups of genes that are co-expressed as well as gene families within a single genome, and among orthologs of multiple species [91][92][93] .…”
Section: Strategies For Application Of Crispr/cas-mediated Cis-enginementioning
confidence: 99%
“…In this work, we found that in vasorelaxing group, the motif length was higher (50 nt) with respect to those detected in the vasocontractile group (18 to 40 nt). Besides, due to vasorelaxing sequences are closer to the transcription starting point (-240 bp on average) than vasocontractile sequences (-590 bp on average), both could have different molecular crowding for the transcription, or distinct interaction modes with cisregulation elements (Gruel et al, 2011).…”
Section: Discussionmentioning
confidence: 99%